ChemInform Abstract: Subtle Impact of Atomic Ratio, Charge and Lewis Basicity on Structure Selection and Stability. The Zint Anion [(La@In2Bi11)(μ‐Bi)2 (La@In2Bi11)]6‐. Issue 6 (20th February 2013) - Weinert, Bastian; Weigend, Florian; Dehnen, Stefanie
Abstract Black, prismatic crystals of [K([2.2.2]crypt)]6{ [La@In2Bi11](μ‐Bi)2 [La@In2Bi11]}·3en·3toluene are synthesized by addition of a suspension of [La(C5Me4H)3] (tris(tetramethylcyclopentadienyl)lanthanum) in toluene to a solution of [K([2.2.2]crypt)]2[InBi3]·en in en (vigorous stirring, 20 °C, 3 h, 11% yield).